Development of Problem-Based E-Worksheet to Train Problem-Solving Skills in Reaction Rate Material - Fadilah, Citra Dia; Yonata, Bertha (Research, Training and Philanthropy Institution Natural Aceh, 2025)
This research aims to develop a PBL-based E-Worksheet to train problem-solving skills in reaction rate materials. The research method employed is the ADDIE model R&D, excluding the implementation stage. Data were obtained from study sheets, validation, activity observations, response questionnaires, as well as pretest and post-test skills. Validity analysis uses a median based on the Likert Scale. The practicality analysis utilizes percentages based on the Guttman Scale, whereas activity observation employs percentages at each meeting. Effectiveness analysis used the interpretation criteria of skill completeness and the N-Gain test. The results of the study showed that the E-Worksheet met the valid criteria, with a median score of 4 in content and construct validation across four categories, practicality as indicated by questionnaire results and activity observation at 95.56%, and effectiveness in practicing problem-solving skills, with an average N-Gain value of 0.87 in the high category. The implications of this study suggest that PBL-based E-Worksheets can serve as an alternative teaching material that supports the development of 21st-century skills, particularly in problem-solving related to reaction rate materials.